SIMUS: An open-source simulator for medical ultrasound imaging. Part II: Comparison with four simulators. (June 2022) - Cigier, Amanda; Varray, François; Garcia, Damien
Highlights: Computational ultrasound imaging has become a well-established methodology in the ultrasound community. We introduce SIMUS, an ultrasound open-source simulator for Matlab, which belongs to the MATLAB ultrasound toolbox (MUST). SIMUS simulates acoustic pressure fields and radiofrequency RF signals for uniform linear or convex probes. SIMUS can contribute to the growing popularization of computational ultrasound imaging. Abstract: Background and Objective: Computational ultrasound imaging has become a well-established methodology in the ultrasound community. In the accompanying paper (part I), we described a new ultrasound simulator (SIMUS) for MATLAB, which belongs to the Matlab UltraSound Toolbox (MUST). SIMUS can generate pressure fields and radiofrequency RF signals for simulations in medical ultrasound imaging. It works in a harmonic domain and uses far-field and paraxial linear equations. Methods: In this article (part II), we illustrate how SIMUS compares with other ultrasound simulators (Field II, k-Wave, FOCUS, and Verasonics) for a homogeneous medium. We designed different transmit sequences (focused, planar, and diverging wavefronts) and calculated the corresponding 2-D and 3-D (with elevation focusing) RMS pressure fields. Results: SIMUS produced pressure fields similar to those of Field II, FOCUS, and k-Wave. The acoustic fields provided by the Verasonics simulator were significantly different from those of SIMUS and k-Wave, although the overall appearance remained consistent. Conclusion: Our simulations tend to demonstrate that SIMUS is reliable and can be used for realistic medical ultrasound simulations.